Amniocentesis increases level of anxiety in women with invasive prenatal diagnosis of Down syndrome - Yanuarita Tursinawati (Universa Medicina, 2015)
Backgound Invasive prenatal diagnosis (PND) through amniocentesis and chorionic villus sampling (CVS) can detect Down syndrome. Pregnant women usually experience a variety of psychological responses associated with invasive PND. This study is intended to assess depression, anxiety and stress levels and the factors related to their psychological responses in pregnant women with invasive prenatal diagnosis of Down syndrome.